A comparison of quality parameters of fresh feline ejaculates collected by three different collection techniques - Jelinkova, Klara; Vitasek, Roman; Novotny, Robert; Bartoskova, Alena (Reproduction in domestic animals, 2018)
The aim of our study was to compare the quality parameters of fresh feline ejaculates collected by three different techniques-urethral catheterization after medetomidine administration (CT), electroejaculation (EE) and epididymal slicing after orchiectomy (EP). A total of 34 adult male cats (Felis catus) were included in the study. In all male cats, the sperm collection was performed under general anaesthesia by three collection methods in the following order: urethral catheterization, electroejaculation and epididymal slicing. The sperm parameters evaluated were as follows: volume, motility, viability, sperm concentration, total sperm count and morphological examination. The highest quality semen parameters were achieved using EE. The comparison of results of the evaluated sperm quality parameters from EE and EP showed significant differences only in one case-the percentage of head abnormalities and lower percentage of head abnormalities were achieved using EE compared to EP: 8.5% (3.0%-21.0%) versus 10.0% (4.0%-22.0%). Semen collected by CT rendered the lowest quality samples when compared to sperm samples collected by EE and EP, especially with respect to the motility and total sperm count which were significantly lower (p < 0.001). Our study showed that sperm samples collected by EE and EP result in better quality of feline ejaculates compared to collection by CT from sperm samples collected from the same male cats. These results demonstrate the necessity of further research of urethral catheterization as a novel technique of semen collection in male cats.
Keywords: kryoprezervace; katetrizace močového měchýře; semen collection; kočky; Cryopreservation; Urinary Catheterization; Electric Stimulation; medetomidin; Orchiectomy; zvířata; Ejaculation; epididymal slicing; analýza spermatu; orchiektomie; Medetomidine; ejakulace; electroejaculation; Male; semen evaluation; urethral catheterization; Semen Analysis; Semen Preservation; uchování spermatu; Specimen Handling; male cat; Cats; odběr biologického vzorku; elektrická stimulace; Animals; mužské pohlaví